Evaluación sensorial y físico- química de un embutido tipo salchicha con sustitución parcial de proteína animal por proteína vegetal: Garbanzos (Cicer arietinum) y arvejas (Pisum sativum) - García Torres, Hugo Alejandro (2025)
The meat industry has envolved in response to the growing demand for healthier and more sustainable products. One of the strategies to improve the nutritional profile of sausages is the incorporation of vegetable proteins such as chickpea (Cicer arietinum) and pea (Pisum sativum). In this context, the present research focuses on the development and evaluation of a sausage with partial substitucion of animal protein with vegetable protein. Four formulations were developed with different proportions of pork and vegetable proteins, analyzing their physicochemical, microbioligical and sensory characteristics. The parameters evaluated include pH, titratable acidity, humidity, Escherichia coli microbial count and organoleptic analysis, which were determined in laboratory tests and sensory evaluations performed by a panel of tasters. This research sought to generate information on the impact of the partial animal protein replacement on sausage quality, contributing to the development of alternative products with potential market acceptance.